Characterization of human fetal brain endothelial cells reveals barrier properties suitable for in vitro modeling of the BBB with syngenic co-cultures. Issue 5 (May 2018) - Andrews, Allison M; Lutton, Evan M; Cannella, Lee A; Reichenbach, Nancy; Razmpour, Roshanak; Seasock, Matthew J; Kaspin, Steven J; Merkel, Steven F; Langford, Dianne; Persidsky, Yuri; Ramirez, Servio H
Endothelial cells (ECs) form the basis of the blood–brain barrier (BBB), a physical barrier that selectively restricts transport into the brain. In vitro models can provide significant insight into BBB physiology, mechanisms of human disease pathology, toxicology, and drug delivery. Given the limited availability of primary human adult brain microvascular ECs ( aBMVEC s), human fetal tissue offers a plausible alternative source for multiple donors and the opportunity to build syngenic tri-cultures from the same host. Previous efforts to culture fetal brain microvascular ECs ( fBMVEC s) have not been successful in establishing mature barrier properties. Using optimal gestational age for isolation and flow cytometry cell sorting, we show for the first time that fBMVEC s demonstrate mature barrier properties. fBMVEC s exhibited similar functional phenotypes when compared to aBMVEC s for barrier integrity, endothelial activation, and gene/protein expression of tight junction proteins and transporters. Importantly, we show that tissue used to culture fBMVEC s can also be used to generate a syngenic co-culture, creating a microfluidic BBB on a chip. The findings presented provide a means to overcome previous challenges that limited successful barrier formation by fBMVEC s. Furthermore, the source is advantageous for autologous reconstitution of the neurovascular unit for next generation in vitro BBB modeling.